Sequences of bovine papillomavirus type 1 DNA--functional and evolutionary implications. - Ahola, H (1983)
A swedish isolate of bovine papillomavirus type 1 (BPV1) was cloned and a 4807 base pairs long sequence was determined, covering the entire late region of the BPV1 genome and strategic parts of the early region. The sequence reveals two large uninterrupted reading frames, designated L1 and L2, which encode tentative polypeptides with molecular weights of 55.5 and 50.0 K. The promoter region for early transcription and the common 3'-end of early transcripts were identified in the sequence by performing S1 nuclease analysis of RNA isolated from a BPV1 transformed cell line. A detailed comparison between the established sequence and sequences from human papillomavirus type 1a (HPV1a) (1) and another BPV1 isolate (2) was also carried out. Only five differences were found when the sequences of the two BPV1 isolates were compared, two of which are located in reading frame L2. The results revealed furthermore that the genomes of BPV1 and HPV1a appear to be organized in a very similar fashion and the homology between reading frames L1 in BPV1 and HPV1 were particularly striking. A comparison of the established BPV1 sequence with sequences from SV40 and polyomavirus revealed no significant homology.